Design, evaluation and validation of an effluent treatment system for the leather tanning process: case Pieles del Sur E.I.R.L. - Muñoz Paz, Víctor; Longa Cuayla, Víctor; Carreño Arispe, Alejandra; Aguilar Franco, José (Enfoque UTE, 2020)
In this project a treatment system for the effluents of a leather tanning process was designed. This system was evaluated based on laboratory tests to ensure its viability, and the treatment was validated by analyzing effluents from the plant already installed. The system has three units: the first one is a Pretreatment that allows the oxidation of sulphides for the liming and draught baths, as well as the precipitation of chromium for the leather tanning baths; the second one is a Physical-Chemical Treatment for the general effluents of the process that allows to obtain treated effluents and decanted solids; the third is a sludge treatment that allows to obtain conditioned and low volume sludge to be collected for final disposal. The analysis of treated effluents showed a considerable reduction in the concentration of polluting chemicals that allows reusing the water and brings the company closer to compliance with the maximum levels allowed.